The Connection between Language and Identity: the Yoruba-Arabic Literates and The Street Urchins of Ibadan - Ibrahim Ismail Ibrahim (Sunan Kalijaga: International Journal of Islamic Civilization, 2022)
The current paper is dedicated to investigate the connection between language and identity, with a special reference to two ambivalent social groups in Ibadan, i.e., the Yoruba-Arab literates and the street urchins. The research shall be carried out with samples of online videos as well as other online resources. One major phenomenon that connects people with varying degrees of social status, religious, ages etc. is the language they speak. In every society, language plays a herculean task in reflecting the identity of the people, and in most times, its usage shows the social class of the speaker. It is incontrovertible that, language and identity go together. We identify people and affiliate them with certain tribe, race or ethnic as the result of language they speak. In other words, we may say, there is no identity without language, this is because the language we speak gives people the opportunity to link us with certain community.